Self-Adaptive Energy-Efficent Applications: The HADAS Developing Approach - Horcas-Aguilera, José Miguel; Pinto-Alarcón, Mónica; Fuentes-Fernández, Lidia; Gámez, Nadia (IEEE, 2017)
Software systems have a strong impact on the energy consumption of the hardware they use. For this reason, software developers should be more aware of the energy consumed by their systems. Moreover, software systems should be developed to be able to adapt their behavior to minimize the energy consumed during their execution. This paper illustrates how to address the problem of developing self-adaptive energyefficient applications using the HADAS approach. HADAS makes use of advanced software engineering methods, such as Dynamic Software Product Lines and Aspect-Oriented Software Development. The main steps of the HADAS approach, both during the design of the application and also at runtime are illustrated by applying them to a running case study.
Keywords: Energía -- Consumo; Energy-efficient applications; Self-adaptation; HADAS repository; Dynamic Software Product Lines; Aspect-Oriented Software Development